2018
DOI: 10.3390/ijms19030780
|View full text |Cite
|
Sign up to set email alerts
|

The Modulatory Roles of N-glycans in T-Cell-Mediated Autoimmune Diseases

Abstract: Glycosylation is a ubiquitous posttranslational modification of proteins that occurs in the endoplasmic reticulum/Golgi. N-glycans and mucin-type O-glycans are achieved via a series of glycohydrolase- and glycosyltransferase-mediated reactions. Glycosylation modulates immune responses by regulating thymocyte development and T helper cell differentiation. Autoimmune diseases result from an abnormal immune response by self-antigens and subsequently lead to the destruction of the target tissues. The modification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 92 publications
0
13
0
Order By: Relevance
“…Treatments with low doses of 2DG do not have toxicity effects even with chronic administration (17), but heart vacuolization has been reported in rats treated with a high dose of 2DG (18). Furthermore, 2DG inhibits N-glycosylation (19), which represents a major immunoregulatory mechanism of Teff cell function (20). Although 2DG decreases glucose utilization both by glycolysis and oxidation in vitro and in vivo (3, 14), it is possible that other functions of 2DG also play a role in reducing autoimmune pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Treatments with low doses of 2DG do not have toxicity effects even with chronic administration (17), but heart vacuolization has been reported in rats treated with a high dose of 2DG (18). Furthermore, 2DG inhibits N-glycosylation (19), which represents a major immunoregulatory mechanism of Teff cell function (20). Although 2DG decreases glucose utilization both by glycolysis and oxidation in vitro and in vivo (3, 14), it is possible that other functions of 2DG also play a role in reducing autoimmune pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Much work in autoimmune disease has focused on understanding the basic mechanisms by which N-glycans determine the pathogenicity of autoantibodies and the immunogenicity of autoantigens. 26,27 Research in relation to the latter has demonstrated that structural variation in cell-surface N-glycans contributes to immune self-recognition. In mice, mutation of Golgi mannosidase II, encoded by the Man2a1 gene, has been shown to reduce complex-type N-glycan branching and to lead to a systemic autoimmune disease similar to lupus in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in N-glycosylation have also been seen in some neurodegenerative diseases such as Alzheimer’s disease, 18 20 Huntington’s disease, 21 and multiple sclerosis. 22 24 However, it is difficult to say whether these are a cause or consequence of the disease.…”
Section: Introductionmentioning
confidence: 99%